1993
DOI: 10.1083/jcb.121.2.283
|View full text |Cite
|
Sign up to set email alerts
|

An ion-transporting ATPase encodes multiple apical localization signals.

Abstract: Abstract. Epithelial cells accumulate distinct popula-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 56 publications
2
61
0
Order By: Relevance
“…GFP fluorescence was generally not observed in the basal membrane that was excluded from analyses. A similar method has previously been used to quantitate the apical to basolateral polarity ratios of Na + -K + -ATPase and H + -K + -ATPase subunits (37). In stably transfected MDCK cells, we obtained similar results using domain selective cell-surface biotinylation and semiquantitative confocal microscopy to determine the ratio of apical to basolateral expression of CFTR (Table 1).…”
Section: Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…GFP fluorescence was generally not observed in the basal membrane that was excluded from analyses. A similar method has previously been used to quantitate the apical to basolateral polarity ratios of Na + -K + -ATPase and H + -K + -ATPase subunits (37). In stably transfected MDCK cells, we obtained similar results using domain selective cell-surface biotinylation and semiquantitative confocal microscopy to determine the ratio of apical to basolateral expression of CFTR (Table 1).…”
Section: Methodssupporting
confidence: 65%
“…Thus, we examined the relative distribution of GFP-CFTR fluorescence in the apical and lateral membranes by semiquantitative confocal microscopy. GFP fluorescence was quantitated in randomly acquired confocal micrograph xz vertical sections as described previously, with minor modifications (37). Using NIH Image software (version 1.57; National Institutes of Health, Bethesda, Maryland, USA), a box (∼2-µm wide and encompassing the length of apical or lateral membranes) was drawn over the region to be measured, and pixel counts within the boxed region were determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coexpression studies in LLC-PK1 cells demonstrated the pres-ence of apical sorting signals in both the ␣ and ␤ subunits (17) of the H,K-ATPase and a basolateral sorting signal in the ␣ 1 subunit of the Na,K-ATPase (6). Sorting signals in both Na,KATPase and H,K-ATPase catalytic subunits were shown to reside in their N-terminal halves (6,17).…”
mentioning
confidence: 99%
“…Sorting signals in both Na,KATPase and H,K-ATPase catalytic subunits were shown to reside in their N-terminal halves (6,17). An apical sorting signal of the H,K-ATPase ␤ subunit was demonstrated to be encoded in its N-glycosylation sites (18).…”
mentioning
confidence: 99%